A Randomized Trial of Home Visitation for CPS-Involved Families: The Moderating Impact of Maternal Depression and CPS History. (August 2018) - Jonson-Reid, Melissa; Drake, Brett; Constantino, John N.; Tandon, Mini; Pons, Laura; Kohl, Patricia; Roesch, Scott; Wideman, Ellie; Dunnigan, Allison; Auslander, Wendy
Home visitation (HV) interventions may hold promise to improve parenting and prevent child maltreatment recidivism in families reported to child protective services (CPS) with young children, but this has rarely been studied. Findings are presented from an 18-month randomized controlled trial in which intact families ( N = 122) with at least one CPS report were provided with a facilitated connection to a paraprofessional evidence-based HV program or usual care services from child protection. Results are reported for changes in maternal stress, depression, and social support outcomes and repeat reports to CPS. No significant changes were found in maternal outcomes by group. Among nondepressed mothers or families without multiple CPS reports prior to study enrollment, HV was associated with a significantly lower likelihood of CPS report recidivism. These results indicate potential for HV to prevent maltreatment recidivism but suggest that higher intensity intervention is warranted for mothers exhibiting significant depressive symptoms or families with extensive CPS histories.